Penentuan Vanadium Secara Spektrofotometri Fosfowolfrovanadat Dalam Batuan Bukit Pianggu Kabupaten Solok - Roswita -; Hamzar Suyani; Safni - (Universitas Andalas, 2008)
ABSTRACT A simple, rapid and accurate Spectrophotometric method described to the determination of vanadium in ore using sodium tungstat as a complexing agent. The method is based on the oxidation of sodium tungstat to form a yellow colored on reaction with vanadium (V), having maximum an absorption occurred at 403 nm. The relative standar deviation of the method for 8 mg/L vanadium (n=11) was 0.24%, and the molar absorptivity is 2.026103 L mol-1cm-1 and sensitivity Sandell is 2.5 10-2 mg cm.2 . The recovery test is 99.47%. The effect of ion interfering Fe (element large amount in ore) on determination is describe. The general procedure which was developed is suittable for determination of 0-20 mg/L of Vanadium and should be applicable to variety of ore sample. Keywords : vanadium, spectrophotometric, sodium tungstat, ore